Modelling off-stream reservoir using rainfall-runoff transformation and satellite rainfall data in Liliba and Manikin watersheds of Indonesia (Kuwait Journal of Science)
Rainwater harvesting (RWH) techniques have become a crucial aspect of human life, enabling the provision of water for household and agricultural needs. Embung, a popular RWH technique in Indonesia's semi-arid regions, has a limited capacity and poses a risk of sedimentation, rendering it unreliable for drought mitigation. An alternative is an off-stream reservoir. It has benefits, including possible placement in locations with less social problems. Reservoirs off-stream have less sedimentation. This study employed Global Satellite Mapping of Precipitation (GSMaP) for the period of 2014–2021 in rainfall-runoff simulations along with the Soil Moisture Accounting (SMA) method of Hydrologic Engineering Center's Hydrologic Modelling System (HEC-HMS) to assess the reliability of off-stream reservoirs in conserving water in Liliba and Manikin watersheds, Kupang, East Nusa Tenggara province of Indonesia. The statistical requirements for calibration and validation include the coefficient of determination (R2 > 0.40), Nash-Sutcliffe Efficiency (NSE >0.40), root mean square error (RMSE)-standard deviation ratio of research data, or RSR (<0.70), and percent bias (PBIAS <30). During calibration, only the percent bias parameter was qualified as excellent (4.01 %), while the other statistical requirements were not met. However, in the validation process, all statistical requirements met satisfactory rating. The results demonstrate that rainfall-runoff simulation could be performed using the GSMaP data in conjunction with the SMA loss method; however, adjustments to HEC-HMS parameters are necessary based on analysis duration and local conditions. The study's modelling indicates that, for five months and three weeks during the dry season in the wet year (2021) and for four months and three weeks during the dry year (2016), water from the off-stream reservoir can supply 5063 residents' household needs in addition to 10 ha of horticultural cultivation. Therefore, the study recommends the utilization of GSMaP satellite data in the inflow simulation of off-stream reservoirs employing the SMA method, particularly in locations lacking adequate rainfall data. © 2025